1998
DOI: 10.1136/jmg.35.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Intrachromosomal triplication of distal 7p.

Abstract: A female infant who died at 2 years of age with growth and psychomotor retardation, wide anterior fontanelle, downward slanting palpebral fissures, large, simple ears, joint dislocation/contractures, recurrent infections, and severe pulmonary hypertension was found to have a de novo 7p+ chromosome. The G banding pattern was suggestive of a triplication of 7p2l.3 and 7p22; results of fluorescence in situ hybridisation studies using a chromosome 7 specific library, a subtelomeric 7p repeat (109A6), and yeast art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…20 21 It is interesting to note that in several cases an unequal distance between two FISH signals (the proximal and the middle versus the middle and the distal) indicated that either the middle segment was inverted or, less likely, the middle segment was in normal orientation, but the proximal and distal segments were inverted,1 4 6 probably, according to the illustrations, the cases of Rauch et al 2 and Harrison et al 3 and the present report. In the other patients, no special attention was paid to the issue of direct versus inverted triplication.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…20 21 It is interesting to note that in several cases an unequal distance between two FISH signals (the proximal and the middle versus the middle and the distal) indicated that either the middle segment was inverted or, less likely, the middle segment was in normal orientation, but the proximal and distal segments were inverted,1 4 6 probably, according to the illustrations, the cases of Rauch et al 2 and Harrison et al 3 and the present report. In the other patients, no special attention was paid to the issue of direct versus inverted triplication.…”
supporting
confidence: 64%
“…This type of triplication has so far been reported for the following chromosomal segments: 2q11.2-q21,7 2q37,25p14-p15.33,3 7p21.2-p21.3,49p13-p22,5 10q26,6 13q14 (present report), and 15q11-q13 120 21 It is interesting to note that in several cases an unequal distance between two FISH signals (the proximal and the middle versus the middle and the distal) indicated that either the middle segment was inverted or, less likely, the middle segment was in normal orientation, but the proximal and distal segments were inverted,1 4 6 probably, according to the illustrations, the cases of Rauch et al 2 and Harrison et al 3 and the present report.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…In all patients tested, the triplication was maternal in origin. Proposed mechanisms include U-type exchanges among three chromatids (Wang et al 1999) or through several different meiotic events occurring sequentially (Rivera et al 1998). Alternatively, triplications may be formed via illegitimate recombination between a normal chromosome 15 and an unstable large SMC(15) intermediary (Schinzel et al 1994).…”
Section: Formation Of Rearrangementsmentioning
confidence: 99%
“…Only a few cases of intrachromosomal triplication have been described [Berry et al, 1990;Holowinsky et al, 1993;Schinzel et al, 1994;Cassidy et al, 1996;Rauch et al, 1996; Devriendt, 1998, personal communication;Harrison et al, 1998;Long et al, 1998;Rivera et al, 1998] These involved chromosomes 2, 5, 7, 10, 15, and 16. We describe the clinical manifestations of our patient, compare them with other cases of tetrasomy 9p, and discuss probable mechanisms causing this chromosomal aberration.…”
Section: Introductionmentioning
confidence: 96%